2002
DOI: 10.1116/1.1520561
|View full text |Cite
|
Sign up to set email alerts
|

Photospeed considerations for extreme ultraviolet lithography resists

Abstract: Photospeed is a prime consideration for wafer throughput of extreme ultraviolet ͑EUV͒ lithography. Faster photoresists additionally provide system advantages such as less thermal management of the mirrors and mask, and potentially increased component lifetimes. However, there are some predicted detrimental considerations when using fast photoresists such as shot noise. In this article, we report details of the formulation of photoresists exposed at 248 nm and identical formulations exposed at 13.4 nm. Composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…If we simply assume the dose noise to go as the square root of the mean dose, a 25% reduction in noise would require a 56% increase in dose. This arguably represents the "shot noise limit" [8][9][10][11][12][13][14][15][16][17][18][19]], yet we find that by biasing the CD by 2 nm we significantly outperform this "limit". Figure 11 shows the corresponding PDFs for the original case in Fig.…”
Section: Predicting Error Ratesmentioning
confidence: 89%
“…If we simply assume the dose noise to go as the square root of the mean dose, a 25% reduction in noise would require a 56% increase in dose. This arguably represents the "shot noise limit" [8][9][10][11][12][13][14][15][16][17][18][19]], yet we find that by biasing the CD by 2 nm we significantly outperform this "limit". Figure 11 shows the corresponding PDFs for the original case in Fig.…”
Section: Predicting Error Ratesmentioning
confidence: 89%
“…However, the advent of several micro exposure tool over the next year has ignited an interest in developing an EUV resist meeting strict tool and performance requirements. For example, the developed resist must possess reasonable photospeed while maintaining a low level of outgassing components [2]. Another factor that has to be considered is the absorption coefficient of resist materials in the EUV.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies on the exposure dose dependence of LER demonstrated that LER decreases with increasing exposure dose. [44][45][46][47] However, it cannot be reduced below a certain value (3-4 nm) when exposure dose is increased. 50,51) A common explanation of this lower limit of LER upon high-dose exposure is that it is of material origin, namely, it is associated with the molecular size and/ or high-order interaction of polymers.…”
Section: Limit Of Lermentioning
confidence: 99%
“…[44][45][46][47][48][49] Equations (2) and (3) indicate that LER is inversely proportional to the square root of exposure dose. Experimental studies on the exposure dose dependence of LER demonstrated that LER decreases with increasing exposure dose.…”
Section: Limit Of Lermentioning
confidence: 99%